The TRAPS apparatus: enhancing target density of nanoparticle beams in vacuum for X-ray and optical spectroscopy - Meinen, Jan; Khasminskaya, S.; Rühl, E.; Baumann, W.; Leisner, Thomas (Aerosol science and technology, 2010)
We present an experimental setup that allows the injection of charged nanoparticles in a diameter range of 3-15 nm into a vacuum chamber and their storage there in an electrodynamic cage. The nanoparticle density in the trap is limited by space charge and can be several orders of magnitude higher than in a free nanoparticle beam. The setup provides for the first time a tool for the application of advanced techniques of spectroscopy to free nanoparticles in this size range. It consists of a combination of (1) a plasma discharge nanoparticle source that generates a high density of nanoparticles of various composition suspended in helium carrier gas at a pressure of about 10-150 mbar, (2) an aerodynamic lens optimized for small particles (diameter 3-15 nm) that forms a well-collimated beam of charged nanoparticles and focuses it into (3) an octopole ion trap operated at low frequencies and filled with helium buffer gas at 10−2 mbar in order to moderate and store the nanoparticles at densities of more than 107 cm−3.